ANALYSIS OF LITERATURE REVIEW ON BUREAUCRACY INTEGRITY IN THE CASE STUDY OF FADIA ARAFIQ'S CORRUPTION - Nurul Trihasanah; Ragil Muhammad Ilham Saputra; Afida Nur Aini; Khoirotul Anisa'; Karunia Syifa Nurani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study examines bureaucratic integrity in relation to regional head corruption, using the case of Fadia Arafiq in Pekalongan Regency as an empirical illustration. The research aims to analyze the concept of bureaucratic integrity from a public administration perspective and to explain how corruption reflects weaknesses in bureaucratic systems. A qualitative approach was employed through a literature review combined with a case study analysis. Data were collected from scientific journals, official reports, and relevant documents published between 2021 and 2026, and analyzed using the Miles and Huberman model, including data condensation, display, and conclusion drawing. The findings reveal that corruption is not solely driven by individual factors but is strongly influenced by systemic weaknesses, such as lack of accountability, weak supervision, and excessive concentration of power. The case demonstrates how monopoly and discretion without proper control create opportunities for abuse of authority. Furthermore, low bureaucratic integrity contributes to declining public trust and poor public service quality. Strengthening transparency, accountability, and ethical values within bureaucratic systems is therefore essential to prevent corruption and improve governance.